Effects of Water Stress and Mulch Type on Linseed Seed Yield, Physiological Traits, and Oil Compounds - Elnaz Moazzamnia; Esmaeil Rezaei-Chiyaneh; Aria Dolatabadian; Otilia Cristina Murariu; Maura Sannino; Gianluca Caruso; Kadambot H. M. Siddique (Crops)
This study investigated the effects of three mulch types (straw, vermicompost and “plastic”) plus an untreated control, and three irrigation regimes (RFD: rainfed conditions; SIF: one supplemental irrigation at the flowering stage; SIVF: two supplemental irrigations at the vegetative and flowering stages) on the growth, seed yield, oil composition, and biochemical status of linseed (Linum usitatissimum L.). Linseed plants were best affected by SIVF and straw mulch in terms of seed yield (300 and 222.4 g m−2, respectively), biomass yield (887.9 and 703 g m−2, respectively), and concentration of oleic and linoleic acids. Under rainfed conditions, “plastic” mulch application increased stearic acid concentrations, while SIF increased palmitic acid concentrations. Rainfed conditions promoted the accumulation of proline (10.1 μmol g−1 fresh weight), total phenols (6.68 mg g−1 fresh weight), and DPPH radical scavenging capacity (56.5%). Under RFD, plants grown in straw-mulched soil showed the highest total phenol content and DPPH radical scavenging capacity, while control (unmulched) plants displayed the highest proline concentration at this irrigation regime. Enzyme activities, including catalase and superoxide dismutase, were enhanced under straw and “plastic” mulch compared to control plants under rainfed conditions. Our findings suggest that straw mulch represents an effective, sustainable strategy to successfully manage linseed crops, mitigating the adverse effects of water deficit stress on plant performance.